Peluang Event Pariwisata Dalam Mengatasi Unsustainability Tourism di Pantai Kelapa Patimban Pusakanagara Kabupaten Subang - R. Hendro S. Arlianto; Evi Novianti; Cipta Endyana (Magister Tourism Study, Faculty of Tourism, Udayana University, 2020)
This study discusses the holding of an